Penyuluhan Pencemaran Lingkungan dan Makanan Sehat dari Ikan di Desa Rantau Baru Kecamatan Pangkalan Kerinci Kabupaten Pelalawan Provinsi Riau - Ridwan Manda Putra; Sukendi Sukendi; Dewita Dewita; Syahril Nedi; Elizal Elizal (PELANTAR PRESS, 2022)
The Extension Activities were done in Rantau Baru Village, Pangkalan Kerinci District, Pelalawan Regency, and was carried out on Thurs and public awareness day 8 September 2022. This community extention aimed providing information to the public about environmental conservation and healthy food of fish. The extension team provided explanations and descriptions of: a) the importance of protecting the environment, b) types of environmental pollution, c) plastic waste and its effects, d) environmental diseases, their causes and remedies. e). Healthy food from fish, so people don't get sick. Participants in this counseling were consists of local government, women group and young in Rantau Baru Village. The participants are representatives from each dusun with a total of 35 participants. The method used in carrying out this activity is to survey the field first, then conduct counseling in the form of interactive lectures and discussions, demonstration of theoretical material through a slide projector and followed by a demonstration of making healthy food from fish, including making fish skin crackers, dinsum fish and fish nuggets. The results of the evaluation of changes in knowledge made to 35 participants in community service activities. 4 people (11.4%) have been able to absorb the material given with very good predicates, 15 people (42.9%) can absorb the material given with good predicate, and 9 people (25.7%) can absorb the material with sufficient predicate and 7 people (20.0%) can absorb the material with less predicate. Based on these data, the community service activities carried out can be said to be successful and show that the impact on the participants is still mastery of science, according to the material provided at the time the service activities are carried out. While the impact on implementation in the field, there has been a process of disseminating knowledge to mothers by the PKK Team on how to make healthy food from fish, and it is hoped that in the future it will develop as a household business which ultimately improves the family economy. Meanwhile, community leaders and village youth work together to tackle waste (especially plastic waste) in Rantau Baru Village.